Synergistic Activity of Colistin Combined With Auranofin Against Colistin-Resistant Gram-Negative Bacteria - Feng, Xiaoxuan; Liu, Shuai; Wang, Yang; Zhang, Yulin; Sun, Lingxiao; Li, Haibo; Wang, Chunlei; Liu, Yingmei; Cao, Bin (Frontiers in Microbiology, 2021)
Colistin-resistant (Col-R) bacteria are steadily increasing, and are extremely difficult to treat. New drugs or therapies are urgently needed to treat infections caused by these pathogens. Combination therapy with colistin and other old drugs, is an important way to restore the activity of colistin. This study aimed to investigate the activity of colistin in combination with the anti-rheumatic drug auranofin against Col-R Gram-negative bacteria. The results of checkerboard analysis demonstrated that auranofin synergized with colistin against Col-R Gram-negative bacteria. Time-kill assays showed significant synergistic antimicrobial activity of colistin combined with auranofin. Electron microscopy revealed that the combination resulted in more cellular structural alterations compared to each drug alone. Auranofin enhanced the therapeutic effectiveness of colistin in mouse peritoneal infection models. These results suggested that the combination of colistin and auranofin might be a potential alternative for the treatment of Col-R Gram-negative bacterial infections.